Design and Development of an Online Assets Inventory Management System (AIMS) (International Journal of Scientific Research and Management (IJSRM), 2017)
: In the age of today, organizations face tremendous challenge in monitoring efficiently the whereabouts, quantity, working condition, depreciation and maintenance status of things of value in their organization. This problem is faced not only by large organizations but also the medium and some smaller organizations. Those things of value known as assets are kept in records by means of inventory. The need to monitor constantly these records of assets cannot be over emphasized as efficient management of the assets inventory of any organization helps maximize the organization’s value by making fixed and intangible assets to be easier to locate, more reliable and efficient. This employs tracking the whereabouts, quantity, working condition, depreciation and maintenance status of assets. This is to have at all times, a detailed list of all assets in the organization displaying their description, serial number, acquisition cost, inventory number, respective location, working condition (status) amongst others. This overcomes the manual-based spreadsheet system, which is characterized by error(s), loss of data, varying reports or results at stages involved in the manual-based spreadsheet system. In this paper, top-down design methodology was used to profers solution to the problem using a number of tools such as PHP and MySQL for the developmental phase. The application was tested and evaluated for usability and functionality using appropriate test data. The front end provides an interactive means for the user of the system to input information into the database. The database (back end) provides a detailed record of all assets in the organization displaying their description, serial number, acquisition cost, inventory number, respective location, working condition (status) amongst others. The complete web-based system could be used from any terminal with internet access. Also, functionality such as updating assets’ details and adding new locations and offices to the database are all possible through the web interface.